2020
DOI: 10.4187/respcare.07154
|View full text |Cite
|
Sign up to set email alerts
|

Overnight Pulse Oximetry to Determine Prognostic Factors in Subjects With Amyotrophic Lateral Sclerosis

Abstract: BACKGROUND: The objective of the current study was to determine whether overnight pulse oximetry in patients with amyotrophic lateral sclerosis is prognostic of the onset of awake respiratory failure and hospital admissions. METHODS: This was an observational study in a cohort of subjects with amyotrophic lateral sclerosis. The study included subjects with a baseline S pO 2 6 94% on home overnight pulse oximetry testing. Patients age 6 80 y and those with comorbidities and with poor short-term prognosis or sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Amongst the sensors currently commercially available, there is a large discrepancy in frequency ranging from one recording per second to one recording every 12 s. This setting affects the results provided by the statistics and the ease of visually inspecting the curves. Beside these limitations, nocturnal pulse oximetry can be used to screen for nocturnal respiratory events [ 15 ], to predict the outcome [ 16 , 17 ], and to monitor patients using NIV at night. Sensibility and specificity are not optimal when pre-test probability of having a specific disease is low.…”
Section: Nocturnal Recordingsmentioning
confidence: 99%
“…Amongst the sensors currently commercially available, there is a large discrepancy in frequency ranging from one recording per second to one recording every 12 s. This setting affects the results provided by the statistics and the ease of visually inspecting the curves. Beside these limitations, nocturnal pulse oximetry can be used to screen for nocturnal respiratory events [ 15 ], to predict the outcome [ 16 , 17 ], and to monitor patients using NIV at night. Sensibility and specificity are not optimal when pre-test probability of having a specific disease is low.…”
Section: Nocturnal Recordingsmentioning
confidence: 99%
“…al describing prognosticating factors for development of respiratory insufficiency in patients with ALS, reported longer diagnostic delay, advanced age at diagnosis, bulbar onset of symptoms, lower FVC, low body mass index and low dyspnea subscore or ALS functional rating scale (ALSFRS-R) were associated with development of respiratory failure (50). Another study reported nocturnal oxygen desaturations were associated with development of respiratory failure and worse prognosis (51).…”
Section: Sleep-related Breathing Disorders In Alsmentioning
confidence: 99%
“…In two recent studies, several factors have been found to be associated with early onset and rapid deterioration of respiratory insufficiency, including higher age at diagnosis, longer diagnostic delay, lower FVC and body mass index, bulbar onset of symptoms, and a lower ALS functional rating scale (ALSFRS-R) total score or dyspnea subscore, respectively [80, 81•]. Another study showed that nocturnal oxygen desaturations are also associated with respiratory failure and worse prognosis [82].…”
Section: Sleep-related Breathing Disordersmentioning
confidence: 99%